Carbon carrier for catalyst, preparation method of carbon carrier, fuel cell catalyst and membrane electrode
By using nitrogen and phosphorus co-doped mesoporous carbon materials as catalyst support, the dispersion and stability of platinum carbon materials in the prior art are solved, and efficient catalyst performance improvement and fuel cell service life are achieved.
Patent Information
- Application Number
- CN202411485028.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
The platinum carbon materials of existing fuel cell catalysts have problems such as poor platinum dispersion, low catalytic activity and insufficient stability, and the proportion of pore structures of commercial carbon supports is small, resulting in poor stability and mass transfer of the catalyst. Moreover, carbon corrosion problems at high potentials will lead to the migration and aggregation of platinum nanoparticles, reducing the stability and activity of the catalyst.
The mesoporous carbon material is used as the catalyst support. By adjusting the precursor and synthesis conditions, the pore structure and doping level of the carbon support are controlled to achieve high mesoporous ratio, excellent graphitization degree and suitable heteroatom doping. Improve the stability and electrochemical properties of the catalyst.
It significantly improves the mass transfer and diffusion ability of the catalyst, extends the service life of the fuel cell, improves the electrical conductivity and corrosion resistance of the catalyst, enhances thermal and chemical stability, and prevents the agglomeration and fall of the active components.
Smart Images

Figure BDA0005098500690000121 
Figure BDA0005098500690000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a carbon carrier for catalyst and a preparation method thereof, a fuel cell catalyst and a membrane electrode. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have attracted much attention due to their high energy conversion efficiency, low pollution emissions and good operating performance. In fuel cells, the membrane electrode assembly (MEA) is the core component for realizing electrochemical reactions, and its performance directly determines the overall efficiency and service life of the fuel cell. One of the key components of the membrane electrode assembly is the catalyst. Currently, the most commonly used is platinum-carbon catalyst. However, platinum resources are scarce and expensive, and there are problems such as active center aggregation, particle growth and shedding during the catalytic process, which leads to a decrease in catalyst performance and a shortened service life. Therefore, improving the utilization and stability of platinum-carbon catalysts is a hot topic and difficulty in current research.
[0003] In order to solve the above problems, the development of new carbon carrier materials is one of the important directions. Carbon materials have many advantages as carriers of platinum-based catalysts: they have a high specific surface area and can provide abundant platinum loading sites; they have good electrical conductivity and are conducive to the rapid transfer of electrons; they have good chemical stability and mechanical strength, so that the catalyst can maintain stable performance under general reaction conditions; and they can also improve the dispersion and stability of the catalyst by regulating its surface properties. At present, a variety of carbon materials have been developed, such as carbon black, activated carbon, carbon nanotubes and graphene. These materials have been widely used in catalysts, but there are still some problems, such as poor platinum dispersion, low catalytic activity, and insufficient stability. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems: the current commercial carbon carrier has a relatively low proportion of mesopores in its pore structure, and platinum is mostly loaded on the surface of the carbon material, resulting in poor stability and mass transfer of the catalyst; secondly, the problem of carbon corrosion under high potential will lead to the migration and aggregation of platinum nanoparticles, reducing the stability and activity of the catalyst; in addition, heteroatom doping on the surface of the carbon carrier has an important influence on the dispersion, stability and activity of the active metal of the catalyst, but currently heteroatom-doped carbon materials are rarely used in catalysts. Therefore, it is necessary to design a carbon carrier that has a high mesopore ratio, an excellent degree of graphitization, and suitable heteroatom doping. However, the preparation methods of carbon carriers that have been reported so far have the problems of high cost, complex process, difficulty in controlling the pore structure ratio or heteroatom doping degree, and a high degree of graphitization will lead to a small specific surface area of the carbon carrier.
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a carbon carrier for catalyst and a preparation method thereof, a fuel cell catalyst and a membrane electrode. The preparation method can obtain a carbon carrier rich in mesopores, ensuring that the pore size of the carrier is mainly mesopores after treatment, and can be regulated within a certain range; the preparation method uses a nitrogen source and a phosphorus source for nitrogen and phosphorus co-doping, and the doping level can be controlled by adjusting the precursor and the synthesis conditions; the preparation method improves the mechanical strength and stability of the carbon carrier through a one-step graphitization treatment; therefore, the carbon carrier obtained by the preparation method can simultaneously have a high mesopore ratio, an excellent degree of graphitization and a suitable heteroatom doping situation. In addition, the preparation method is simple, efficient, universal and can be scaled up in batches.
[0006] A first aspect of an embodiment of the present invention provides a method for preparing a carbon support for a fuel cell catalyst, comprising the following steps:
[0007] S1, mixing a carbon source, a nitrogen source, a phosphorus source and a template agent uniformly to obtain a mixture; wherein the template agent is selected from at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina; the mass ratio of the template agent to the carbon source is (0.1-15):1;
[0008] S2, calcining the mixture to obtain a calcined product;
[0009] S3, stirring the calcined product in an acid solution, and then filtering, washing and drying to obtain a carbon carrier.
[0010] The advantages and technical effects brought by the preparation method of the first aspect of the embodiment of the present invention are:
[0011] (1) The preparation method of the first aspect of the embodiment of the present invention can obtain a nitrogen-phosphorus co-doped mesoporous carbon material, which can simultaneously have the following characteristics: a mesoporous structure with adjustable pore size, a high degree of graphitization, and appropriate nitrogen and phosphorus doping. The carbon material can be used as a carrier to prepare a catalyst to significantly improve the relevant performance:
[0012] ① The pore structure of this carbon carrier is mainly mesopores, and the pore size can be flexibly controlled, which enhances the mass transfer and diffusion capacity of the catalyst. At the same time, it also increases the intrapore loading ratio of active metal particles such as platinum, which can effectively prevent the agglomeration and shedding of active components during the reaction process and improve the stability of the catalyst.
[0013] ② The carbon carrier has a high degree of graphitization, which improves the conductivity and corrosion resistance of the catalyst. The improved conductivity helps to improve the transmission efficiency of electrons, thereby improving the overall electrochemical performance. The enhanced corrosion resistance helps to improve the durability of the catalyst in harsh working environments and extend the service life of the fuel cell.
[0014] ③ Appropriate nitrogen and phosphorus doping can improve the electronic structure and provide better electronic conductivity; in addition, appropriate nitrogen and phosphorus doping has a good anchoring effect, which helps to evenly disperse the active components of the catalyst, reduce aggregation, and increase the effective catalytic area; in addition, nitrogen and phosphorus co-doping can enhance the thermal stability and chemical stability of the carbon carrier.
[0015] (2) The preparation method of the first aspect of the embodiment of the present invention can effectively regulate the pore size distribution of the carbon carrier by controlling the mass ratio of the template agent to the carbon source. When the mass ratio of the template agent to the carbon source is less than 0.1:1, the specific surface area of the obtained carbon carrier is too small, and the pore structure is underdeveloped, which is not conducive to the active metal loading and the catalyst mass transfer. When the mass ratio of the template agent to the carbon source is greater than 15:1, the specific surface area of the obtained carbon carrier is too large, it is not easy to graphitize, and the catalyst durability is poor.
[0016] (3) The preparation method of the first aspect of the embodiment of the present invention can effectively control the pore size distribution of the carbon carrier by controlling the type of the template to be at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina. When the template is other types, it may not be possible to obtain a carbon carrier with a high mesoporous ratio.
[0017] (4) The preparation methods in the related art in the past have limitations, and it is impossible to obtain a carbon carrier with a high mesopore ratio, excellent graphitization degree, and suitable heteroatom doping through a single preparation process. The preparation method of the first aspect of the embodiment of the present invention can obtain the target product after acid washing by adjusting the ratio of the carbon source, template, nitrogen source, and phosphorus source, and controlling the carbonization temperature and time. The preparation method is simple and efficient, the template cost is low, and it is conducive to large-scale production and application.
[0018] In some embodiments, in step S1, the template is selected from at least two of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina.
[0019] In some embodiments, in step S1, the template agent is selected from at least two of magnesium citrate, magnesium gluconate, magnesium acetate and zinc oxide nanorods.
[0020] In some embodiments, in step S1, the template is a mixture of magnesium citrate and zinc oxide nanorods, wherein the mass ratio of magnesium citrate to zinc oxide nanorods is (2.5-3.5):1.
[0021] In some embodiments, in step S1, the mass ratio of the template to the carbon source is (2-10):1.
[0022] In some embodiments, in step S1, the mass ratio of the template to the carbon source is (2-6):1.
[0023] In some embodiments, in step S1, the carbon source includes at least one of sucrose, polyethylene terephthalate, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylamide, phenolic resin and polymethyl acrylate.
[0024] In some embodiments, in step S1, the nitrogen source includes at least one of urea, ethylenediamine, dopamine, sodium nitrate, potassium nitrate, pyridine, melamine and nitrobenzene.
[0025] In some embodiments, in step S1, the phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, sodium tripolyphosphate, trimethyl phosphate, diethyl phosphate and triethyl phosphate.
[0026] In some embodiments, in step S1, the mass ratio of the nitrogen source to the carbon source is (0.2-10):1; and / or the mass ratio of the nitrogen source to the phosphorus source is (1-10):1.
[0027] In some embodiments, in step S1, the mass ratio of the nitrogen source to the carbon source is (0.5-5):1; and / or the mass ratio of the nitrogen source to the phosphorus source is (1-5):1.
[0028] In some embodiments, in step S2, the holding temperature of the calcination treatment is 1200-2500° C., and the holding time of the calcination treatment is 1-12 hours.
[0029] In some embodiments, in step S2, the holding temperature of the calcination treatment is 1500-1800° C., and the holding time of the calcination treatment is 1-5 hours.
[0030] In some embodiments, in step S2, the calcination treatment atmosphere is selected from at least one of nitrogen, argon, water vapor, carbon dioxide and ammonia.
[0031] A second aspect of an embodiment of the present invention provides a carbon carrier for a fuel cell catalyst, which is obtained by the preparation method of the first aspect of an embodiment of the present invention.
[0032] The advantages and technical effects of the carbon support for fuel cell catalysts in the second aspect of the embodiment of the present invention are as follows:
[0033] Since the preparation method of the first aspect of the embodiment of the present invention is adopted, the obtained carbon carrier is a nitrogen-phosphorus co-doped mesoporous carbon material, which can simultaneously have the following characteristics: a mesoporous structure with adjustable pore size, a high degree of graphitization, and appropriate nitrogen and phosphorus doping. The use of this carbon carrier to prepare a catalyst can significantly improve the relevant performance:
[0034] ① The pore structure of this carbon carrier is mainly mesopores, and the pore size can be flexibly controlled, which enhances the mass transfer and diffusion capacity of the catalyst. At the same time, it also increases the intrapore loading ratio of active metal particles such as platinum, which can effectively prevent the agglomeration and shedding of active components during the reaction process and improve the stability of the catalyst.
[0035] ② The carbon carrier has a high degree of graphitization, which improves the conductivity and corrosion resistance of the catalyst. The improved conductivity helps to improve the transmission efficiency of electrons, thereby improving the overall electrochemical performance. The enhanced corrosion resistance helps to improve the durability of the catalyst in harsh working environments and extend the service life of the fuel cell.
[0036] ③ Appropriate proportions of nitrogen and phosphorus doping can improve the electronic structure and provide better electronic conductivity; in addition, appropriate nitrogen and phosphorus doping has a good anchoring effect, which helps to evenly disperse the active components of the catalyst, reduce aggregation, and increase the effective catalytic area; in addition, nitrogen and phosphorus co-doping can enhance the thermal and chemical stability of the carbon carrier.
[0037] In some embodiments, the specific surface area of the carbon material is 300 to 1200 m 2 / g, the mesopore volume is 0.5~2.0m 3 / g, the most likely pore size distribution is 3-20nm and can be adjusted, and the pore volume of the 3-20nm pore size is 0.5-2.5cm 3 / g, the graphite crystallite range is 0.5-5nm, the electrical conductivity is 6-13S / cm, the nitrogen content is 0.5-4%, the phosphorus content is 0.5-3%, and the nitrogen-phosphorus content ratio is (1-4):1.
[0038] A third aspect of the embodiments of the present invention provides a fuel cell catalyst, comprising the carbon carrier of the second aspect of the embodiments of the present invention and an active metal supported on the carbon carrier.
[0039] The advantages and technical effects brought by the fuel cell catalyst of the third aspect of the embodiment of the present invention are:
[0040] Since the carbon carrier of the second aspect of the embodiment of the present invention is used, the catalyst of the third aspect of the embodiment of the present invention has strong mass transfer and diffusion capabilities, good catalyst stability, high conductivity and corrosion resistance, that is, the catalyst has good electrochemical performance and durability.
[0041] In some embodiments, the active metal includes platinum, and based on the total mass of the catalyst being 100%, the loading amount of the platinum is 10-70 wt%.
[0042] A fourth aspect of the embodiments of the present invention provides a fuel cell membrane electrode, comprising the catalyst of the third aspect of the embodiments of the present invention.
[0043] The advantages and technical effects brought by the membrane electrode of the fourth aspect of the embodiment of the present invention are:
[0044] Since the catalyst of the third aspect of the embodiment of the present invention is used, the membrane electrode of the fourth aspect of the embodiment of the present invention has excellent electrochemical performance and a long service life. DETAILED DESCRIPTION
[0045] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0046] A first aspect of an embodiment of the present invention provides a method for preparing a carbon support for a fuel cell catalyst, comprising the following steps:
[0047] S1, mixing a carbon source, a nitrogen source, a phosphorus source and a template agent uniformly to obtain a mixture; wherein the template agent is selected from at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina; the mass ratio of the template agent to the carbon source is (0.1-15):1;
[0048] S2, calcining the mixture to obtain a calcined product;
[0049] S3, stirring the calcined product in an acid solution, and then filtering, washing and drying to obtain a carbon carrier.
[0050] The preparation method of the first aspect of the embodiment of the present invention can obtain a nitrogen-phosphorus co-doped mesoporous carbon material, which can simultaneously have the following characteristics: a mesoporous structure with adjustable pore size, a high degree of graphitization, and a suitable proportion of nitrogen and phosphorus doping. The carbon material can be used as a carrier to prepare a catalyst to significantly improve the relevant performance:
[0051] ① The pore structure of this carbon carrier is mainly mesopores, and the pore size can be flexibly controlled, which enhances the mass transfer and diffusion capacity of the catalyst. At the same time, it also increases the intrapore loading ratio of active metal particles such as platinum, which can effectively prevent the agglomeration and shedding of active components during the reaction process and improve the stability of the catalyst.
[0052] ② The carbon carrier has a high degree of graphitization, which improves the conductivity and corrosion resistance of the catalyst. The improved conductivity helps to improve the transmission efficiency of electrons, thereby improving the overall electrochemical performance. The enhanced corrosion resistance helps to improve the durability of the catalyst in harsh working environments and extend the service life of the fuel cell.
[0053] ③ Appropriate proportions of nitrogen and phosphorus doping can improve the electronic structure and provide better electronic conductivity; in addition, appropriate nitrogen and phosphorus doping has a good anchoring effect, which helps to evenly disperse the active components of the catalyst, reduce aggregation, and increase the effective catalytic area; in addition, nitrogen and phosphorus co-doping can enhance the thermal and chemical stability of the carbon carrier.
[0054] The preparation method of the first aspect of the embodiment of the present invention can regulate the pore size distribution of the carbon carrier by controlling the mass ratio of the template agent to the carbon source. When the mass ratio of the template agent to the carbon source is less than 0.1:1, the specific surface area of the obtained carbon carrier is too small, the pore structure is not developed, which is not conducive to the active metal loading and the catalyst mass transfer. When the mass ratio of the template agent to the carbon source is greater than 15:1, the specific surface area of the obtained carbon carrier is too large, it is not easy to graphitize, and the catalyst durability is poor.
[0055] In the preparation method of the first aspect of the embodiment of the present invention, the nitrogen source and the phosphorus source are added using different substances, and the mass ratio of the nitrogen source and the phosphorus source can be flexibly controlled. By controlling the mass ratio of the nitrogen source and the phosphorus source, the doping content of nitrogen and phosphorus can be effectively regulated to obtain a carbon carrier with a suitable nitrogen-phosphorus ratio, which plays the best synergistic role and improves the activity and durability of the catalyst. If a substance containing both a nitrogen source and a phosphorus source is used as a doping raw material, the above effect cannot be achieved.
[0056] The preparation method of the first aspect of the embodiment of the present invention can effectively regulate the pore size distribution of the carbon carrier by controlling the type of the template to be at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina. When the template is other types, a carbon carrier with a high mesoporous ratio may not be obtained.
[0057] The preparation methods in the related art in the past have limitations, and it is impossible to obtain a carbon carrier with a high mesopore ratio, excellent graphitization degree, and suitable heteroatom doping through a single preparation process. The preparation method of the first aspect of the embodiment of the present invention can obtain the target product after acid washing by regulating the ratio of the carbon source, template, nitrogen source, and phosphorus source, and controlling the carbonization temperature and time. The preparation method is simple and efficient, the template cost is low, and it is conducive to large-scale production and application.
[0058] In the preparation method of the embodiment of the present invention, in step S1, the template is selected from at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina. Preferably, in some embodiments, the template is selected from at least two of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina. According to the particle size and shape of the template, at least two templates are preferably involved in the preparation, and a multi-level pore structure carbon carrier rich in at least two pore structures can be obtained. The presence of a multi-level pore structure can ensure that the carbon carrier has a larger specific surface area and provides more loading sites for the catalyst; on the other hand, it can ensure that the carbon carrier has a suitable pore size distribution, which is conducive to the transmission of protons and oxygen. More preferably, the template is selected from at least two of magnesium citrate, magnesium gluconate, magnesium acetate and zinc oxide nanorods. Further preferably, the template is a mixture of magnesium citrate and zinc oxide nanorods, wherein the mass ratio of magnesium citrate to zinc oxide nanorods is (2.5-3.5):1, for example, 2.5:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1, 3.5:1, etc.
[0059] In the preparation method of the embodiment of the present invention, in step S1, the mass ratio of the template to the carbon source is (0.1-15):1, for example, 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, etc. Preferably, in some embodiments, the mass ratio of the template to the carbon source is (2-10):1, and the mass ratio of the template to the carbon source can obtain a carbon carrier with a suitable specific surface area and pore structure within the above range. When the mass ratio of the template to the carbon source is too small, it is not conducive to increasing the specific surface area of the carbon carrier, nor is it conducive to increasing the pore structure ratio, nor is it conducive to active metal loading, nor is it conducive to catalyst mass transfer, and thus is not conducive to improving the electrochemical performance of the catalyst. When the mass ratio of the template to the carbon source is too large, the specific surface area of the carbon material is too large, and it is not easy to graphitize, which is not conducive to improving the durability of the catalyst. More preferably, the mass ratio of the template to the carbon source is (2-6):1.
[0060] In some embodiments, in step S1, the carbon source, nitrogen source and phosphorus source may be uniformly mixed first, and then the mixture of the three and the template may be uniformly mixed. Such step-by-step mixing helps to evenly disperse various raw materials, thereby improving the uniformity of nitrogen and phosphorus doping.
[0061] In some embodiments, in step S1, the carbon source may include but is not limited to at least one of sucrose, polyethylene terephthalate, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylamide, phenolic resin and polymethyl acrylate.
[0062] In some embodiments, in step S1, the nitrogen source may include but is not limited to at least one of urea, ethylenediamine, dopamine, sodium nitrate, potassium nitrate, pyridine, melamine and nitrobenzene.
[0063] In some embodiments, in step S1, the phosphorus source may include but is not limited to at least one of phosphoric acid, sodium dihydrogen phosphate, sodium tripolyphosphate, trimethyl phosphate, diethyl phosphate and triethyl phosphate.
[0064] In some embodiments, in step S1, the mass ratio of the nitrogen source to the carbon source is (0.2-10):1, for example, 0.2:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.; and / or, the mass ratio of the nitrogen source to the phosphorus source is (1-10):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. The mass ratio of the nitrogen source to the carbon source and / or the phosphorus source is regulated to obtain a suitable nitrogen and phosphorus doping amount and to achieve a better synergistic effect. When the mass ratio of the nitrogen source to the carbon source and / or the phosphorus source is too small, it is not conducive to increasing the nitrogen and phosphorus doping amount of the prepared carbon carrier and is not conducive to the dispersion of the active metal. When the mass ratio of the nitrogen source to the carbon source and / or the phosphorus source is too large, the nitrogen and phosphorus doping amount of the prepared carbon carrier is too high, which will destroy the structural stability of the carbon carrier and is not conducive to improving the stability and durability of the catalyst. Preferably, the mass ratio of the nitrogen source to the carbon source is (0.5-5):1, and / or the mass ratio of the nitrogen source to the phosphorus source is (1-5):1, and the optimal nitrogen and phosphorus doping amount can be obtained.
[0065] In some embodiments, in step S2, the holding temperature of the calcination treatment is 1200-2500°C, such as 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, etc., and the holding time of the calcination treatment is 1-12h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc. When the holding temperature of the calcination treatment is too low, it is not conducive to improving the graphitization degree of the carbon carrier, thereby not conducive to improving the conductivity and corrosion resistance of the carbon carrier. When the holding temperature of the calcination treatment is too high, the graphitization degree of the carbon carrier is too high, which is not conducive to the loading of the catalyst active components. Preferably, in step S2, the holding temperature of the calcination treatment is 1500-1800° C., and the holding time of the calcination treatment is 2-5 hours, so that a carbon carrier with a high degree of graphitization and a suitable specific surface area can be obtained at the same time.
[0066] In some embodiments, in step S2, the calcination treatment atmosphere is selected from at least one of nitrogen, argon, water vapor, carbon dioxide and ammonia.
[0067] In some embodiments, in step S3, the acid comprises at least one of hydrochloric acid, nitric acid, sulfuric acid, formic acid, acetic acid, citric acid and gluconic acid. The calcined product is soaked in an acid solution to remove the template and obtain a mesoporous carbon carrier.
[0068] A second aspect of an embodiment of the present invention provides a carbon carrier for a fuel cell catalyst, which is obtained by the preparation method of the first aspect of an embodiment of the present invention.
[0069] Since the preparation method of the first aspect of the embodiment of the present invention is adopted, the obtained carbon carrier is a nitrogen-phosphorus co-doped mesoporous carbon material, which can simultaneously have the following characteristics: a mesoporous structure with adjustable pore size, a high degree of graphitization, and a suitable proportion of nitrogen and phosphorus doping. The use of this carbon carrier to prepare a catalyst can significantly improve the relevant performance:
[0070] ① The pore structure of this carbon carrier is mainly mesopores, and the pore size can be flexibly controlled, which enhances the mass transfer and diffusion capacity of the catalyst. At the same time, it also increases the intrapore loading ratio of active metal particles such as platinum, which can effectively prevent the agglomeration and shedding of active components during the reaction process and improve the stability of the catalyst.
[0071] ② The carbon carrier has a high degree of graphitization, which improves the conductivity and corrosion resistance of the catalyst. The improved conductivity helps to improve the transmission efficiency of electrons, thereby improving the overall electrochemical performance. The enhanced corrosion resistance helps to improve the durability of the catalyst in harsh working environments and extend the service life of the fuel cell.
[0072] ③ Appropriate proportions of nitrogen and phosphorus doping can improve the electronic structure and provide better electronic conductivity; in addition, appropriate nitrogen and phosphorus doping has a good anchoring effect, which helps to evenly disperse the active components of the catalyst, reduce aggregation, and increase the effective catalytic area; in addition, nitrogen and phosphorus co-doping can enhance the thermal and chemical stability of the carbon carrier.
[0073] In some embodiments, the specific surface area of the carbon material is 300 to 1200 m 2 / g, and the large specific surface area can provide abundant attachment sites for active metals.
[0074] In some embodiments, the mesopore volume of the carbon material is 0.5 to 2.0 m 3 / g, accounting for more than 80% of the total pore volume, the most likely pore size distribution is in the range of 3 to 20 nm, more preferably in the range of 3 to 15 nm, and can be adjusted. Among them, the pore size of 3 to 6 nm is more conducive to the intrapore loading of active metal particles, which can effectively inhibit the shedding, migration and agglomeration of active metal particles and avoid being poisoned by polymers. The pore size of 6 to 15 nm is more conducive to the transmission of water and gas, and can improve the mass transfer efficiency. The graphite crystallite range of the carbon material is 2 to 5 nm, and the higher degree of graphitization structure has excellent electronic conductivity, which helps to increase the electrochemical reaction rate, and exhibits better corrosion resistance, which can slow down the attenuation of catalyst performance.
[0075] In some embodiments, the carbon material has an electrical conductivity ranging from 6 to 13 S / cm as measured by a four-probe conductivity method at 10 MPa.
[0076] In some embodiments, the carbon material has a nitrogen content of 0.5-4%, a phosphorus content of 0.5-3%, and a nitrogen-phosphorus content ratio of (1-4):1. Co-doping with nitrogen and phosphorus in appropriate proportions can enhance the interaction between the metal catalyst and the carrier, thereby improving the dispersibility and stability of the catalyst; it can also adjust the electronic structure of the catalyst and optimize its adsorption capacity and reaction kinetics for reactants. The doping content of nitrogen and phosphorus can be effectively regulated by controlling the mass ratio of the nitrogen source to the phosphorus source. When the mass ratio of the nitrogen source to the phosphorus source is less than 1:1, the obtained carbon carrier has a poor dispersion effect when preparing the catalyst and is easy to agglomerate. When the mass ratio of the nitrogen source to the phosphorus source is greater than 4:1, the catalyst prepared by the obtained carbon carrier has poor durability.
[0077] A third aspect of the embodiments of the present invention provides a fuel cell catalyst, comprising the carbon carrier of the second aspect of the embodiments of the present invention and an active metal supported on the carbon carrier.
[0078] Since the carbon carrier of the second aspect of the embodiment of the present invention is used, the catalyst of the third aspect of the embodiment of the present invention has strong mass transfer and diffusion capabilities, good catalyst stability, high conductivity and corrosion resistance, that is, the catalyst has good electrochemical performance and durability.
[0079] In some embodiments, the fuel cell catalyst is a platinum-based catalyst, the platinum loading of the platinum-based catalyst can be 10-70wt%, with a crystallite diameter of 2.5-6.0nm on the platinum (200) crystal plane, and the platinum loaded in the pores of the carbon carrier accounts for 50wt% or more of the total amount of platinum in the catalyst. Most of the platinum is loaded inside the pores of the carbon carrier, which can effectively reduce the possibility of the catalyst being poisoned, and the platinum particles are not easy to agglomerate and fall off, further improving the activity and durability of the catalyst.
[0080] Regarding the preparation method of the platinum-based catalyst, any method in the relevant technology can be adopted. For example: the carbon carrier of the second aspect of the embodiment of the present invention can be added to a dispersant for dispersion, and then a platinum-containing precursor is added to continue dispersing, and then a reducing agent is added and stirred. After the reaction, the platinum-based catalyst is obtained by washing and drying. The preparation method of the platinum-based catalyst listed above can evenly disperse the metal platinum on the inner and outer surfaces of the carbon carrier, thereby improving the catalytic effect of the catalyst; in addition, the preparation method is simple and efficient, and is convenient for promotion and application in industrial production.
[0081] Regarding the preparation method of platinum-based catalysts, the dispersant can be at least one of water, ethanol, ethylene glycol, isopropanol and n-propanol, etc. The aforementioned dispersants are beneficial to uniformly disperse the carbon carrier and the platinum-containing precursor, and then make the metallic platinum evenly distributed on the carbon carrier to ensure the performance of the catalyst.
[0082] A fourth aspect of the embodiments of the present invention provides a fuel cell membrane electrode, comprising the catalyst of the third aspect of the embodiments of the present invention.
[0083] Since the catalyst of the third aspect of the embodiment of the present invention is used, the membrane electrode of the fourth aspect of the embodiment of the present invention has excellent electrochemical performance and a long service life.
[0084] The present invention is described in detail below with reference to embodiments.
[0085] Example 1
[0086] Weigh 6g of polyvinyl alcohol, 6g of urea, and 3g of phosphoric acid, grind them finely and mix them evenly in a mortar, add 12g of magnesium citrate to the mixture and continue grinding and mixing until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace, and treat it at 1500℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir it for 12h to remove the template, and wash, filter, and dry to obtain the target product.
[0087] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the obtained dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0088] Example 2
[0089] Weigh 6g sucrose, 6g melamine, and 3g phosphoric acid, grind them finely and mix them evenly in a mortar, add 18g magnesium gluconate to the mixture and continue grinding and mixing until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace, and treat it at 1800℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir for 12h to remove the template, and wash, filter, and dry to obtain the target product.
[0090] Take 0.45g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add chloroplatinic acid containing 1.05g of platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the obtained dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 70% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0091] Example 3
[0092] Weigh 6g of polyvinyl alcohol, 6g of ethylenediamine, and 3g of sodium dihydrogen phosphate, grind them finely and mix them evenly in a mortar, add 12g of magnesium citrate and 12g of magnesium acetate to the mixture and continue grinding and mixing until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace, and treat it at 1800℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir it for 12h to remove the template, and wash, filter, and dry to obtain the target product.
[0093] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the obtained dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0094] Example 4
[0095] Weigh 6g of polyvinyl alcohol, 6g of urea, and 3g of phosphoric acid, grind them finely and mix them evenly in a mortar, add 12g of magnesium citrate and 8g of magnesium acetate to the mixture and continue grinding and mixing until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace, and treat it at 1600℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir it for 12h to remove the template, and wash, filter, and dry to obtain the target product.
[0096] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the obtained dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0097] Example 5
[0098] The preparation method of this embodiment is the same as that of Example 1, except that 12 g of magnesium acetate is used in this embodiment instead of 12 g of magnesium citrate in Example 1.
[0099] The physical properties of the nitrogen and phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the platinum-based catalyst prepared are shown in Table 2.
[0100] Example 6
[0101] The preparation method of this embodiment is the same as that of Example 1, except that a mixture of 6 g of magnesium citrate and 6 g of magnesium acetate is used in this embodiment instead of 12 g of magnesium citrate in Example 1.
[0102] The physical properties of the nitrogen and phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the platinum-based catalyst prepared are shown in Table 2.
[0103] Example 7
[0104] The preparation method of this embodiment is the same as that of embodiment 1, except that a mixture of 6 g of magnesium citrate and 6 g of zinc oxide nanorods is used in this embodiment instead of 12 g of magnesium citrate in embodiment 1.
[0105] The physical properties of the nitrogen and phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the platinum-based catalyst prepared are shown in Table 2.
[0106] Example 8
[0107] The preparation method of this embodiment is the same as that of embodiment 1, except that a mixture of 9 g of magnesium citrate and 3 g of zinc oxide nanorods is used in this embodiment instead of 12 g of magnesium citrate in embodiment 1.
[0108] The physical properties of the nitrogen and phosphorus co-doped mesoporous carbon prepared in this example are shown in Table 1, and the physical properties of the platinum-based catalyst prepared are shown in Table 2.
[0109] Comparative Example 1
[0110] Weigh 6g of polyvinyl alcohol, add 12g of magnesium citrate and grind and mix in a mortar until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace and treat it at 1500℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir for 12h to remove the template, and then wash, filter and dry to obtain the target product.
[0111] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the resulting dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this comparative example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0112] Comparative Example 2
[0113] Weigh 6g of polyvinyl alcohol, 6g of urea, and 3g of phosphoric acid, grind them finely in a mortar and mix them evenly. Put the powder into a high-temperature sintering furnace, and treat it at 1500℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, put the heat-treated product into a pH 1 HCl aqueous solution and stir for 12h, and then wash, filter, and dry to obtain the target product.
[0114] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the resulting dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this comparative example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0115] Comparative Example 3
[0116] Weigh 6g of polyvinyl alcohol, 6g of urea, and 3g of phosphoric acid, grind them finely and mix them evenly in a mortar, add 35g of magnesium citrate to the mixture and continue grinding and mixing until it is mixed into a uniform powder. Put the powder into a high-temperature sintering furnace, and treat it at 1500℃ for 2h under an argon atmosphere to obtain a heat-treated product. Finally, the heat-treated product is placed in a pH 1 HCl aqueous solution and stirred for 12h to remove the template, and the target product is obtained after washing, filtering, and drying.
[0117] Take 0.5g of carbon material and add it to 100mL of ultrapure water and stir it thoroughly for 3h, then add 0.5g of chloroplatinic acid containing platinum and continue stirring for 4h. Then add ethylene glycol to the mixed solution and stir it thoroughly for 1h. After stirring, wash and filter the resulting dispersion repeatedly to make the filtrate neutral. After vacuum drying the filter cake, a platinum-based catalyst supported by a nitrogen-phosphorus co-doped mesoporous carbon carrier with a platinum loading of 50% is obtained. The physical properties of the nitrogen-phosphorus co-doped mesoporous carbon prepared in this comparative example are shown in Table 1, and the physical properties of the obtained platinum-based catalyst are shown in Table 2.
[0118] Comparative Example 4
[0119] The preparation method of this comparative example is the same as that of Example 1, except that 65 g of urea is used in this comparative example instead of 6 g of urea in Example 1.
[0120] The physical properties of the nitrogen and phosphorus co-doped mesoporous carbon prepared in this comparative example are shown in Table 1, and the physical properties of the prepared platinum-based catalyst are shown in Table 2.
[0121] Comparative Example 5
[0122] The preparation method of this comparative example is the same as that of Example 1, except that 12 g of nano-Fe2O3 is used in this comparative example instead of 12 g of magnesium citrate in Example 1.
[0123] The physical properties of the nitrogen and phosphorus co-doped carbon material prepared in this comparative example are shown in Table 1, and the physical properties of the prepared platinum-based catalyst are shown in Table 2.
[0124] Table 1. Physical properties of nitrogen and phosphorus co-doped mesoporous carbon obtained in the above examples and comparative examples
[0125]
[0126] Table 2. Physical properties of platinum-based catalysts obtained in the above examples and comparative examples
[0127]
[0128]
[0129] Among them, Example 6 uses a dual template process of magnesium citrate and magnesium acetate. Compared with Example 1 and Example 5 using a single template, the MEA performance of Example 6 is better. This is because the dual template method of magnesium citrate and magnesium acetate can obtain a carbon carrier rich in two pore size distributions according to the size of the template agent, among which the pore size of 3-6nm is more conducive to the pore loading of platinum particles, which can effectively avoid the migration, agglomeration and shedding of platinum. The pore size of 6-15nm is more conducive to the transmission of water and gas, which can improve the mass transfer efficiency.
[0130] Example 7 uses a dual template process of magnesium citrate and zinc oxide nanorods. Compared with Example 6 using a dual template of magnesium citrate and magnesium acetate, Example 7 has better RDE durability and MEA performance. This is because the synergistic effect of magnesium citrate and zinc oxide nanorods is better, and a carbon carrier rich in mesopores and through-pore distribution can be obtained according to the size and shape of the template agent. The mesopore pore size is more conducive to the intrapore loading of platinum particles, which can effectively avoid the migration, agglomeration and shedding of platinum. Through-pores have a more significant effect on the improvement of mass transfer capacity. Example 8 further optimizes the ratio of template agents magnesium citrate and zinc oxide nanorods. Compared with Example 7, RDE durability and MEA performance are further improved.
[0131] By comparing Example 1 with Comparative Example 1, it can be seen that in Comparative Example 1, due to the absence of doping with nitrogen and phosphorus elements, the prepared carbon carrier has poor loading and dispersion capabilities for platinum.
[0132] By comparing Example 1 and Comparative Example 2, it can be seen that in Comparative Example 2, since no template is used, the pore structure of the carbon material is not well developed, resulting in fewer platinum loading sites and poor mass transfer capacity, which leads to unsatisfactory MEA performance.
[0133] By comparing Example 1 and Comparative Example 3, it can be seen that in Comparative Example 3, the proportion of the template is increased, the specific surface area of the carbon material is too large, the graphitization degree of the finally treated carbon carrier is low, and the corrosion resistance is poor, resulting in poor durability of the catalyst.
[0134] By comparing Example 1 and Comparative Example 4, it can be seen that in Comparative Example 4, the proportion of the nitrogen source is increased, the nitrogen and phosphorus content ratio of the carbon material is too large, the synergy is poor, and the overall structural stability of the carrier is reduced, resulting in poor durability of the catalyst.
[0135] By comparing Example 1 and Comparative Example 5, it can be seen that in Comparative Example 5, iron oxide is used as a template, and the prepared catalyst is prone to carry iron impurities. Iron ions will react with active sites, causing catalyst poisoning, further affecting catalyst activity and durability.
[0136] In summary, the preparation method of the embodiment of the present invention has the following advantages:
[0137] (1) A carbon support having a high mesopore ratio, excellent graphitization degree, and suitable heteroatom doping can be prepared by a one-step synthesis method. The method adjusts the ratio of carbon source, template, nitrogen source, and phosphorus source, controls the heat treatment temperature and time, and obtains the target product after acid washing. Due to the support of the template, the graphitization treatment will not cause the structure of the carbon material to collapse. After obtaining a certain degree of graphitization, the material can still maintain a large specific surface area and a high mesopore ratio.
[0138] (2) By using a dual-template or multi-template process, a multi-level pore structure carbon material rich in at least two pore sizes or pore structures can be obtained. The presence of multi-level pores can ensure a larger specific surface area, providing more loading sites for the catalyst; on the other hand, it can ensure a suitable pore size distribution, which is conducive to the transmission of protons and oxygen.
[0139] (3) The pore size distribution of the carbon carrier is regulated by controlling the mass ratio of the template and the carbon source and the heat treatment temperature. Similarly, nitrogen and phosphorus doping is regulated by the mass ratio of the nitrogen source, phosphorus source and carbon source, and the degree of graphitization can be regulated by temperature. The preparation method is simple and efficient, with low raw material cost, which is conducive to large-scale production and application.
[0140] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0141] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a carbon support for a fuel cell catalyst, characterized in that: The following steps are involved: S1, mixing a carbon source, a nitrogen source, a phosphorus source and a template agent uniformly to obtain a mixture; wherein the template agent is selected from at least one of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina; the mass ratio of the template agent to the carbon source is (0.1-15):1; S2, calcining the mixture to obtain a calcined product; S3, stirring the calcined product in an acid solution, and then filtering, washing and drying to obtain a carbon carrier.
2. The preparation method according to claim 1, characterized in that: In step S1, the template agent is selected from at least two of magnesium oxide, magnesium hydroxide, magnesium citrate, magnesium gluconate, magnesium acetate, basic magnesium carbonate, zinc oxide nanorods, titanium dioxide and mesoporous alumina; Preferably, the template agent is selected from at least two of magnesium citrate, magnesium gluconate, magnesium acetate and zinc oxide nanorods; More preferably, the template is a mixture of magnesium citrate and zinc oxide nanorods, wherein the mass ratio of magnesium citrate to zinc oxide nanorods is (2.5-3.5):
1.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the template to the carbon source is (2-10):1; Preferably, the mass ratio of the template to the carbon source is (2-6):
1.
4. The preparation method according to claim 1, characterized in that: In step S1, the carbon source includes at least one of sucrose, polyethylene terephthalate, polyimide, polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylamide, phenolic resin and polymethyl acrylate; Optionally, the nitrogen source includes at least one of urea, ethylenediamine, dopamine, sodium nitrate, potassium nitrate, pyridine, melamine and nitrobenzene; Optionally, the phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, sodium tripolyphosphate, trimethyl phosphate, diethyl phosphate and triethyl phosphate.
5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the nitrogen source to the carbon source is (0.2-10):1; and / or the mass ratio of the nitrogen source to the phosphorus source is (1-10):1; Preferably, the mass ratio of the nitrogen source to the carbon source is (0.5-5):1; and / or the mass ratio of the nitrogen source to the phosphorus source is (1-5):
1.
6. The preparation method according to claim 1, characterized in that: In step S2, the holding temperature of the calcination treatment is 1200-2500° C., and the holding time of the calcination treatment is 1-12 hours; Preferably, the holding temperature of the calcination treatment is 1500-1800° C., and the holding time of the calcination treatment is 1-5 hours; Optionally, the calcination atmosphere is selected from at least one of nitrogen, argon, water vapor, carbon dioxide and ammonia.
7. A carbon support for a fuel cell catalyst, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.
8. The carbon carrier according to claim 7, characterized in that The specific surface area of the carbon material is 300 to 1200 m 2 / g, the mesopore volume is 0.5~2.0m 3 / g, the most likely pore size distribution is 3-20nm and can be adjusted, and the pore volume of the 3-20nm pore size is 0.5-2.5cm 3 / g, the graphite crystallite range is 0.5-5nm, the electrical conductivity is 6-13S / cm, the nitrogen content is 0.5-4%, the phosphorus content is 0.5-3%, and the nitrogen-phosphorus content ratio is (1-4):
1.
9. A fuel cell catalyst, characterized in that: Comprising the carbon carrier according to claim 7 or 8 and an active metal supported on the carbon carrier; Preferably, the active metal includes platinum, and based on the total mass of the catalyst being 100%, the loading amount of the platinum is 10 to 70 wt%.
10. A fuel cell membrane electrode, characterized in that: Comprising the catalyst according to claim 9.
Citation Information
Cited By
Carrier material and preparation method thereof
CN118790978A